PENGEMBANGAN VIDEO PEMBELAJARAN UNTUK MENINGKATKAN MINAT BELAJAR SISWA PADA MATERI PERSILANGAN MONOHIBRID DAN DIHIBRID(DEVELOPMENT OF A LEARNING VIDEO TO INCREASE STUDENTS’ INTEREST IN LEARNING MONOHYBRID AND DIHYBRID CROSSES) - Zulfah, Kayla Fatimah; Sari, Yusiana Fatika; Rahma, Aida Aulia; Al Zenyta, Navynda Fiza (Universitas Negeri Yogyakarta, 2025)
Learning media is one of the most important aspects of the learning process for students. However, students have different learning styles, so the learning media must vary to meet all students' needs. In this study, learning media is developed as videos containing learning material content accompanied by animation. The media used in learning is designed through long stages so that the media can be used optimally. The purpose of this study is to describe the design and development process of learning media in the form of videos on monohybrid and dihybrid crossbreeding material for grade 3 high school with the Four-D (4-D) model. This study uses a descriptive method to describe the application of the modified 4-D model. The study results indicate that the developed learning videos have met the valid criteria and are ready to be used in learning. In addition, respondents also showed a positive response to the developed learning videos. The results of this study can be used by teachers or students to be used as media in learning.